Nanoparticle‐mediated targeting of autoantigen peptide to cross‐presenting liver sinusoidal endothelial cells protects from CD8 T‐cell‐driven autoimmune cholangitis. Issue 4 (7th January 2021) - Carambia, Antonella; Gottwick, Cornelia; Schwinge, Dorothee; Stein, Stephanie; Digigow, Reinaldo; Şeleci, Muharrem; Mungalpara, Disha; Heine, Markus; Schuran, Fenja A.; Corban, Carlotta; Lohse, Ansgar W.; Schramm, Christoph; et al.
Summary: Autoimmune diseases are caused by adaptive immune responses to self‐antigens. The development of antigen‐specific therapies that suppress disease‐related, but not unrelated immune responses in general, is an important goal of biomedical research. We have previously shown that delivery of myelin peptides to liver sinusoidal endothelial cells (LSECs) using LSEC‐targeting nanoparticles provides effective protection from CD4 T‐cell‐driven autoimmune encephalomyelitis. Here, we investigated whether this methodology might also serve antigen‐specific treatment of a CD8 T‐cell‐driven autoimmune disease. As a model for CD8 T‐cell‐mediated autoimmunity, we used OT‐1 T‐cell‐driven cholangitis in K14‐OVAp mice expressing the cognate MHC I‐restricted SIINFEKL peptide in cholangiocytes. To study whether peptide delivery to LSECs could modulate cholangitis, SIINFEKL peptide‐conjugated nanoparticles were administered intravenously one day before transfer of OT‐1 T cells; five days after cell transfer, liver pathology and hepatic infiltrates were analysed. SIINFEKL peptide‐conjugated nanoparticles were rapidly taken up by LSECs in vivo, which effectively cross‐presented the delivered peptide on MHC I molecules. Intriguingly, K14‐OVAp mice receiving SIINFEKL‐loaded nanoparticles manifested significantly reduced liver damage compared with vehicle‐treated K14‐OVAp mice. Mechanistically, treatment with LSEC‐targeting SIINFEKL‐loaded nanoparticles significantly reduced the number of liver‐infiltrating OT‐1 T cells, which up‐regulated expression of the co‐inhibitory receptor PD‐1 and down‐regulated cytotoxic effector function and inflammatory cytokine production. These findings show that tolerogenic LSECs can effectively internalize circulating nanoparticles and cross‐present nanoparticle‐bound peptides on MHC I molecules. Therefore, nanoparticle‐mediated autoantigen peptide delivery to LSECs might serve the antigen‐specific treatment of CD8 T‐cell‐driven autoimmune disease. Abstract : We show that CD8 T‐cell‐mediated bile duct damage can be prevented by targeting the specific epitope peptides to liver sinusoidal endothelial cells in vivo using nanoparticles. These cells effectively cross‐present the received peptides and induce CD8 T‐cell tolerance.